Response Fruit Flies to Methyl Eugenol Trap Heights in Guava Orchards in Rawamerta, Karawang, West Java - Apriliyana, Nabilla Yusran; Siriyah, Siti Latifatus; Saputro, Nurcahyo Widyodaru; Herawani, Febrina; Abadi, Slamet (Jurnal Biologi Tropis, 2026)
Guava is a popular fruit commodity widely cultivated in Indonesia due to its refreshing taste and suitability for tropical climates. Several commonly cultivated guava varieties include water apple (Syzygium aqueum), crystal guava (Psidium guajava), and Malay apple (Syzygium malaccense). During its cultivation, guava crops often face constraints from fruit fly (Bactrocera sp.) infestations, which can diminish both the quality and quantity of the harvest. Conventional control practiced by farmers typically involves wrapping the fruit in plastic; however, this method is considered inefficient and potentially increases plastic waste. Therefore, eco-friendly control alternatives are required, such as the utilization of attractant traps. This study aimed to determine the most effective attractant trap height for capturing fruit flies. The research employed a single-factor Randomized Complete Block Design (RCBD) with five trap height treatments: P1 (100 cm), P2 (150 cm), P3 (200 cm), P4 (250 cm), and P5 (300 cm) above ground level, with five replications each. Data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level if significant differences were observed. The results indicated that the different trap heights significantly affected the number of fruit flies captured. The 300 cm trap height treatment yielded the highest catch, with a total of 521 fruit flies. Furthermore, five Bactrocera species were identified among the trapped population: Bactrocera carambolae, Bactrocera correcta, Bactrocera kandiensis, Bactrocera dorsalis, and Bactrocera occipitalis, with Bactrocera carambolae being the most dominant species. Key words: Attractant, fruit flies, guava, trap height